Death and a maiden : infanticide and the tragical history of Grethe Schmidt - Myers, William David (DeKalb : Northern Illinois University Press, 2011)
"On the feast of St. Michael, September 1659, a thirteen-year-old peasant girl left her family's rural home to work as a maid in the nearby city of Brunswick. Just two years later, Grethe Schmidt found herself imprisoned and accused of murdering her bastard child. Filled with political intrigue, Death and a Maiden tells a fascinating story that began in the bedchamber of a house in Brunswick and ended at the court of Duke Augustus in the city of Wolfenbüttel. No one was ever able to prove conclusively that Grethe had been pregnant and no infant's body was ever found to justify her prosecution. But, from one accusation, Grethe's tale spiraled outward to set a defense lawyer and legal theorist against powerful city magistrates and then upward to a legal contest between that city and its overlord, the Duchy of Brunswick, with the city's ancient liberties hanging in the balance. Myers weaves the story of Grethe's arrest, torture, trial, and sentence for "suspected infanticide," into a detailed account of the workings of the criminal system in continental Europe, including the nature of interrogations, the process of torture, and the creation of a "criminal" identity over time. He presents an in-depth examination of a system in which torture was both legal and an important part of criminal investigations. This story serves as a captivating slice of European history as well as a highly informative look at the condition of poor women and the legal system in mid-17th century Germany. General readers and scholars alike will be riveted by Grethe's ordeal."--Publisher's website
In Brunswick, near Hannover City -- Anatomy of a crime -- A girl, purportedly a maiden -- Family values -- Common repute, women and neighbors -- Corpus delicti -- Knowledgeable women, the midwive's tale -- Legal maneuvering and the question of torture -- Terror, torture, and Grethe Schmidt -- Case for a defense -- Not even a sow, the case for Grethe -- The thick wilderness of lies -- The way to a confession -- "Even to the devil himself" -- Conclusion: many vigorous enemies.
Includes bibliographical references (pages 251-262) and index.
Print version record.
JSTOR
Keywords: Schmidt, Grethe, -- 1646 or 1647- -- Trials, litigation, etc; Schmidt, Grethe, -- 1646 or 1647-; Schmidt, Grethe -- 1646-; Infanticide -- Germany -- Braunschweig -- History -- 17th century; Infanticide -- Germany -- Braunschweig -- Case studies; Trials (Infanticide) -- Germany -- Braunschweig -- Case studies; Infanticide -- Allemagne -- Brunswick -- Histoire -- 17e siècle.; Infanticide -- Allemagne -- Brunswick -- Études de cas; Procès (Infanticide) -- Allemagne -- Brunswick -- Études de cas; Infanticide; Trials; Trials (Infanticide); Germany -- Braunschweig; Kindesmord; Prozess; 1600-1699; Trials, litigation, etc; Case studies; History